2013
DOI: 10.1152/jn.01072.2012
|View full text |Cite
|
Sign up to set email alerts
|

The training schedule affects the stability, not the magnitude, of the interlimb transfer of learned dynamics

Abstract: The way that a motor adaptation is trained, for example, the manner in which it is introduced or the duration of the training period, can influence its internal representation. However, recent studies examining the gradual versus abrupt introduction of a novel environment have produced conflicting results. Here we examined how these effects determine the effector specificity of motor adaptation during visually guided reaching. After adaptation to velocity-dependent dynamics in the right arm, we estimated the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
72
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 85 publications
8
72
3
1
Order By: Relevance
“…Thus, our behavioral findings considering the right arm retest performance could be explained by a superposition of competing motor memories of task A and task B [43]. Recent investigations as well as our results indicate that subjects transfer approximately 10–30% of learning to the contralateral side which alters the forward model of the task [9–11]. Combining the (negative) contralateral transfer effect of task B onto retest of task A with the decrement due to temporal factors qualitatively accounts for the distinct reduction of task A motor memory at retest in the ABA-schedule.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, our behavioral findings considering the right arm retest performance could be explained by a superposition of competing motor memories of task A and task B [43]. Recent investigations as well as our results indicate that subjects transfer approximately 10–30% of learning to the contralateral side which alters the forward model of the task [9–11]. Combining the (negative) contralateral transfer effect of task B onto retest of task A with the decrement due to temporal factors qualitatively accounts for the distinct reduction of task A motor memory at retest in the ABA-schedule.…”
Section: Discussionmentioning
confidence: 83%
“…Other studies have reported no difference in the influence of the schedule of perturbation presentation on motor learning of other types of perturbations, in either healthy (Wang et al 2011; Joiner et al 2013; Patrick et al 2014) or impaired (Gibo et al 2013; Schlerf et al 2013) participants. In contrast, abruptly introduced perturbations were shown to strengthen interlimb transfer (Malfait and Ostry, 2004).…”
Section: Discussionmentioning
confidence: 87%
“…Afterwards, in certain movements, the subjects’ trajectories were disrupted by velocity-dependent curl force-fields (FFs). We assessed the level of adaptation using error-clamp (EC) trials (i.e., we measured the force pattern that subjects produced when their lateral errors were held to near zero values in an error-clamp) [10, 35–38]. Adaptation rates were calculated by obtaining the difference between the adaptation coefficient ( x ) [10, 35–38] for the EC trial following the first FF trial in a measurement cycle ( EC Post ) and the adaptation coefficient for the EC trial preceding this force-field trial ( EC Pre ): italicAdaptation Rate=xfalse(ECPostfalse)−xfalse(ECPrefalse)Learning environments with different levels of consistency (operationally defined as the lag-1 autocorrelation ( R (1)) of the environment) and variability were created to study the environmental modulation of adaptation rate.…”
Section: Methodsmentioning
confidence: 99%
“…We assessed the level of adaptation using error-clamp (EC) trials (i.e., we measured the force pattern that subjects produced when their lateral errors were held to near zero values in an error-clamp) [10, 35–38]. Adaptation rates were calculated by obtaining the difference between the adaptation coefficient ( x ) [10, 35–38] for the EC trial following the first FF trial in a measurement cycle ( EC Post ) and the adaptation coefficient for the EC trial preceding this force-field trial ( EC Pre ): italicAdaptation Rate=xfalse(ECPostfalse)−xfalse(ECPrefalse)Learning environments with different levels of consistency (operationally defined as the lag-1 autocorrelation ( R (1)) of the environment) and variability were created to study the environmental modulation of adaptation rate. italicConsistency:.3emRfalse(1false)=Efalse[false(FFn−μFFfalse)false(FFn+1−μFFfalse)false]/σFF2In the anti-consistent environment (P1N1; R (1)=−0.3), 21 subjects experienced to 50 cycles each with a single positive FF trial, followed by a single negative FF trial, followed by 11–13 washout (null) trials.…”
Section: Methodsmentioning
confidence: 99%